THE EFFECT OF BABY MASSAGE ON THE SLEEP QUALITY OF 3-12 MONTHS BABIES IN PRIVATE MIDWIVE JAMBI CITY - Atika Fadhilah Danaz Nasution; Nuraidah; Imelda (NSC Nursing, 2021)
Introduction: Sleep needs in infants 3-12 months are not only in terms of quantity but also quality. Good quality sleep provides benefits to the fulfilment of physical and psychological needs. One method of meeting these needs is baby massage. A common reason for mothers to give baby massages is the child's habit of fussing at night and often waking up, and they say that after the massage, their child becomes calm at night. This study aims to analyze the effect of baby massage on the sleep quality of infants aged 3-12 months at private midwife Muji Kenali Asam in Jambi City.